Total Plate Count and Organoleptic Tests of Soft Cheese Made from Goat Milk with the Addition of Lemon Juice (Citrus limon) - Viaretika, Baiq; Sulistyowati, Endang; Dohi, Muhammad; Haryanto, Haryanto; Soetrisno, Edi; Ali, Muhammad; Hidayat, Hidayat; Akbarillah, Tris (Universitas Bengkulu, 2024)
This study evaluates the effect of adding local lemon juice (Citrus limon) on Total Plate Count (TPC) and organoleptic in soft cheese, including color, texture, taste and preference for color, aroma/smell, texture and flavour. The experimental design used was a Completely Randomized Design (CRD) using four treatments and 4 replications. Treatments differed by lemon juice concentration: T1 (0%), T2 (2%), T3 (4%), T4 (6%). The observation variables are TPC and organoleptic. The research results show that adding local lemon juice significantly effects (P<0.01) on the TPC and Organoleptics of color, texture, taste, and preferences for color, aroma/aroma, texture and flavour. The highest mean TPC was obtained at T1 (0%) with a value of 4.08 x 108 cfu/g, and the lowest was at T4 (6%) with a value of 2.25 x 108 cfu/g.